New Progress in Angiogenesis Therapy of Cardiovascular Disease by Ultrasound Targeted Microbubble Destruction - Liao, Yang-Ying (Hindawi Publishing Corporation, 2014)
Angiogenesis plays a vital part in the pathogenesis and treatment of cardiovascular disease and has become one of the hotspots that are being discussed in the past decades. At present, the promising angiogenesis therapies are gene therapy and stem cell therapy. Besides, a series of studies have shown that the ultrasound targeted microbubble destruction (UTMD) was a novel gene delivery system, due to its advantages of noninvasiveness, low immunogenicity and toxicity, repeatability and temporal and spatial target specificity; UTMD has also been used for angiogenesis therapy of cardiovascular disease. In this review, we mainly discuss the combination of UTMD and gene therapy or stem cell therapy which is applied in angiogenesis therapy in recent researches, and outline the future challenges and good prospects of these approaches.